Do Financial Risks affect Financial Performance of Listed Insurance Firms in Nigeria? - Ogunsola, Adebowale (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The study assessed the effect of financial risks on the financial performance of listed insurance firms in Nigeria. The population of this study consists of all listed insurance firms in Nigeria. However, ten (10) insurance firms were selected as sample. The selection of these insurance firms was done using judgmental sampling technique. Data for the study were extracted from their annual reports covering 10 years, from 2015 to 2021. Panel data method was employed for analysis using E-view 10.0. Results revealed that only liquidity risk (LDR) has negative and significant effect on financial performance, while the effect of credit risk and leverage risk is insignificant among the sampled insurance firms. It is concluded that liquidity risk tends to significantly impair the financial performance, if not properly monitored and mitigated. Following this, the study recommends that the sampled insurance firms should continually develop and implement risk management policies and strategies that will help reduce their risk profile in order to improve their financial performance.